A novel rhombohedron rolling mechanism. (November 2016) - Xun, Zhiyuan; Yao, Yan-an; Li, Yezhuo; Tian, Yaobin; Sun, Xuemin; Liu, Xiaoping
Abstract: In this paper, a novel multi-loop-coupled mechanism of three degrees of freedom (DOFs) with a rhombohedron shape is presented. The mechanism is composed of six identical mechanisms, which are formed by an octothorp-shaped structure. Based on the corresponding relationship between the mechanism and rhombohedron, the DOF is analyzed by the assembly process of face-units. By kinematic analysis, the center of mass (CM) of the mechanism can be derived. The rolling capability is analyzed by using the Zero-Moment-Point (ZMP) theory. By deforming its shape, this mechanism can realize the gait of going straight, direction adjustment, and climbing slope. Since the structure is symmetrical in nature, its locomotion capability is identical when any of its six faces touches the ground. Two additional postures (surveillance and hiding postures) of the mechanism can increase its surviving ability in the wild. A prototype is manufactured, and rolling experiments are carried out to verify the functions of the mechanism. Highlights: A novel multi-loop coupled mechanism with a rhombohedron shape is designed. Isotropic locomotion capability is achieved by symmetrical structure. The gait of going straight, direction adjustment, climbing slope are analyzed. Surveillance and hiding postures can increase its surviving ability in the wild